1995
DOI: 10.1128/jb.177.15.4266-4271.1995
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the Campylobacter jejuni porin

Abstract: The major outer membrane protein (MOMP) of Campylobacter jejuni was purified to homogeneity by selective solubilization and fast protein liquid chromatography. The amino acid composition of the MOMP indicates the presence of cysteine residues. The amino-terminal sequence, determined over 31 residues, shows no significant homology with any other porin from gram-negative bacteria except in a discrete region. Immunocross-reactivity between Escherichia coli OmpC and the MOMP was analyzed, and a common antigenic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 42 publications
11
93
2
Order By: Relevance
“…Preparation of the antiserum. Polyclonal antibodies were raised in rabbit using purified MOMP, and used as previously described (Bolla et al, 1995). This antiserum is able to recognize the various monomeric and oligomeric forms of C. jejuni MOMP, in analogy to a previous report concerning the OmpF porin of Escherichiu coli (Pagks and Bolla, 1988).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preparation of the antiserum. Polyclonal antibodies were raised in rabbit using purified MOMP, and used as previously described (Bolla et al, 1995). This antiserum is able to recognize the various monomeric and oligomeric forms of C. jejuni MOMP, in analogy to a previous report concerning the OmpF porin of Escherichiu coli (Pagks and Bolla, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…The Campylobacter porin was purified to homogeneity according to Bolla et al (1995). Briefly, after successive washing, the bacterial pellet was sonicated and selective solubilization of the membranes conserved only the outer membrane fraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, salicylate has been shown to decrease the susceptibility of bacteria, such as E. coli, to antimicrobials by altering membrane proteins and inducing efflux pumps (Price et al, 2000). Since C. jejuni possesses an outer-membrane protein (MOMP) belonging to the same porin family as E. coli OmpF (Bolla et al, 1995) and a multidrug efflux pump (CmeABC) belonging to the same RND family as AcrAB-TolC (Lin et al, 2002), it has been speculated that salicylate might also decrease antimicrobial accumulation in C. jejuni. A previous study by Randall et al (2003) showed a small but significant effect of salicylate on the ciprofloxacin resistance of Campylobacter, and our results confirm a 2-to 4-fold increase in MIC values for ciprofloxacin in almost all strains, with ciprofloxacin-susceptible strains and their respective variants reacting alike.…”
Section: Effect Of Sodium Salicylatementioning
confidence: 99%